ZIPK activates the IL‐6/STAT3 signaling pathway and promotes cisplatin resistance in gastric cancer cells. Issue 9 (22nd August 2021) - Fan, Haonan; Ou, Qifeng; Su, Qiao; Li, Guanman; Deng, Zhijuan; Huang, Xiaohui; Bi, Jiong
Abstract : Gastric cancer is one of the most common malignant cancers globally. Chemotherapy resistance remains a major obstacle in the treatment of gastric cancer, and the molecular mechanisms underlying drug resistance are still not well understood. We previously reported that Zipper interacting protein kinase (ZIPK), also known as death‐associated protein kinase3, exerts an oncogenic effect on gastric cancer via activation of Akt/NF‐κB signaling and promotion of stemness. Here, we explored the roles of ZIPK in cisplatin resistance. We report that ZIPK enhances cell proliferation and invasion and reduces the antitumor activity of cisplatin in gastric cancer. In addition, our western blot data suggest that ZIPK activated the IL‐6/STAT3 signaling pathway. Furthermore, ZIPK increased the expression of IL‐6 and multidrug‐resistance genes. Using the STAT3 inhibitor stattic to block the IL‐6/STAT3 signaling pathway strongly increased the sensitivity of ZIPK‐expressed cells to cisplatin. In conclusion, ZIPK may play a role in cisplatin resistance through activation of the IL‐6/ STAT3 signaling pathway. Inhibition of STAT3 in gastric cancer overexpressing ZIPK might have potential to improve the efficacy of cisplatin. Abstract : ZIPK activates the IL‐6/STAT3 signaling pathway via Ser727 phosphorylation in gastric cancer cells and increases IL‐6‐induced STAT3‐dependent transcription. Effective blockade of STAT3 activity by the STAT3 inhibitor stattic sensitized gastric cancer cells to cisplatin and reduced expression of the cisplatin resistance‐related genes G3BP2, THOC1, ATP7A, and OTUD1 .